The Revolutionary Role of Abulcasis in the History of Surgery - Baker, Diya; Abdallah, Yusuf (International Journal of Human and Health Sciences (IJHHS), 2019)
The Islamic golden era was named as such in recognition of the advancement of human knowledge in addition to the efficacy at which it took place. A time which spanned the late 7th century until the early 14th century saw the illumination of medical practices and transmission of the scriptures to Europe. This naturally led to the rise of renaissance science. Arab intelligentsias such as Avicenna and Abulcasis were the driving gears behind this movement.Abulcasis, born in Andalucía in the year 936 AD, is renowned for delivering his innovations in a thirty-volume medical and surgical encyclopaedia known as ‘Kitab Al Tasrif’ which translates to the Book of Concessions. Housed within, are the roots of many modern-day technologies that are still used and a base of knowledge that was beyond his time. In a time where Europe’s biggest library held a mere thirty-six volumes, Abulcasis was designing one device after the other. The discrepancy in knowledge between the East and the West was made more apparent when one of Abulcasis’ innovations, the vaginal speculum, was not fully understood and one of its parts were erroneously deemed to be for decoration.His excellence in areas of obstetrics and gynaecology, breast surgery, herbal medicine and neurosurgery were made clear throughout his discussions within Kitab Al Tasrif. He was also a keen educator as he strived to encourage the then-tabooed study of anatomy post-mortem.Abulcasis truly had a significant effect on today’s medicine and surgery. International Journal of Human and Health Sciences Vol. 04 No. 01 January’20 Page : 8-14